Wirausaha Pembuatan Kue Kering untuk Meningkatkan Keterampilan Hidup Anak Tunarungu - Fatmawati Fatmawati; Nurhastuti Nurhastuti; Yarmis Hasan (Universitas Negeri Padang, 2018)
This paper discusses about improving life skills for students with hearing impairment by providing the skills of entrepreneurship to make cookies. The skills of making cookies for the teachers who teaching the students with hearing impairment in Padang is expected to be a source of income that can finance the life of the students. This research used case study approach which is reseacher analyzed the problem and managed the elternative solution. Implementation methods of this training included lectures, demonstrations and training, as well as mentoring and monitoring and evaluation. The results show that the entrepreneur of pastries training can increase the ability of life of students with hearing impairment. In addition, the economic value of making cookies has high expected to provide the maximum benefit for the students with hearing impairment.